Bloodstream infection caused by Bacteroides denticanum, a close relative of Bacteroides pyogenes, misidentified by MALDI TOF- mass spectrometry - Tkadlec, Jan; Krutova, Marcela; Matejkova, Jana; Nyc, Otakar; Drevinek, Pavel (Anaerobe, 2018)
Bacteroides pyogenes can cause infections in humans. We describe a case of bloodstream infection caused by Bacteroides denticanum that probably originated from a dog bite. MALDI-TOF MS misidentified this new species as B. pyogenes. Subsequent analysis using the 16S rRNA sequencing approach identified the species as B. denticanum.
Keywords: Bacteroides; Animals; Female; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; ženské pohlaví; infekce bakteriemi rodu Bacteroides; lidé; Bacteremia; Dogs; bakteriemie; Aged; Bacteroides Infections; Bacterial Typing Techniques; techniky typizace bakterií; spektrometrie hmotnostní - ionizace laserem za účasti matrice; senioři; zvířata; psi; Humans